2018
DOI: 10.1038/s41598-018-28538-z
|View full text |Cite
|
Sign up to set email alerts
|

GABA promotes gastrin-releasing peptide secretion in NE/NE-like cells: Contribution to prostate cancer progression

Abstract: In prostate cancer (PCa), neuroendocrine cells (NE) have been associated with the progression of the disease due to the secretion of neuropeptides that are capable of diffusing and influence surrounding cells. The GABAergic system is enriched in NE-like cells, and contributes to PCa progression. Additionally, γ-aminobutyric acid (GABA) stimulates the secretion of gastrin-releasing peptide (GRP) in peripheral organs. For the first time, in this study we show the role of GABA and GABAB receptor 1 (GABBR1) expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
(60 reference statements)
2
14
0
Order By: Relevance
“…The relationship between GABRG1 and cancer has not yet been reported. Presently, using enrichment analysis, we confirmed that the GABAergic system contributes to PCa progression [39]. It has also been reported that GABA is highly expressed in prostate tissue of patients with cancer or benign prostatic hypertrophy and the high expression has been observed in prostate tissue of cancer patients with LNM [66].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The relationship between GABRG1 and cancer has not yet been reported. Presently, using enrichment analysis, we confirmed that the GABAergic system contributes to PCa progression [39]. It has also been reported that GABA is highly expressed in prostate tissue of patients with cancer or benign prostatic hypertrophy and the high expression has been observed in prostate tissue of cancer patients with LNM [66].…”
Section: Discussionsupporting
confidence: 74%
“…Neuroactive ligand-receptor interaction, especially the GABAergic system, has significant effects on the progression of PCa. The GABAergic system is enriched in neuroendocrine cell- (NE-) like cells [38] and contributes to PCa progression due to the secretion of neuropeptides [39].…”
Section: Resultsmentioning
confidence: 99%
“…The participation of androgens in several physiological and pathological processes in the CNS has been widely described (5). It is also known that they are involved in prostate, colon and lung cancer growth (11, 1921). Epidemiological data report that GBM occur in a greater proportion in men than in women (3:2), which suggests androgens participation in the development of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ubiquitin-mediated proteolysis, endocytosis, and focal adhesion pathways can impact PCa development and progression in different ways [4547]. In addition, in the GABAergic synapse pathway, GABA induces GRP secretion via GABBR1 in neuroendocrine-like cells, which is involved in PCa progression [48]. The cell cycle is a vital cellular process involving DNA replication and translation, and it tends to be deregulated in cancer [49].…”
Section: Discussionmentioning
confidence: 99%